Evaluation of MYC status in oral lichen planus in patients with progression to oral squamous cell carcinoma. (8th July 2013) - Segura, S.; Rozas‐Muñoz, E.; Toll, A.; Martín‐Ezquerra, G.; Masferrer, E.; Espinet, B.; Rodriguez, M.; Baró, T.; Barranco, C.; Pujol, R.M.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Malignant transformation of oral lichen planus (OLP) to oral squamous cell carcinoma (OSCC) is controversial. Clinical and histological features of OLP lesions have limited prognostic value. What does this study add? OLP lesions from patients with progression to OSCC show MYC gains and C‐MYC overexpression, not present in OLP lesions from patients without evolution to OSCC. Determining MYC status on some OLP lesions may predict a subgroup of patients with a higher risk of progression to OSCC.